2016
DOI: 10.20473/j.djmkg.v49.i3.p168-174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soy isoflavone genistein on orthodontic tooth movement in guinea pigs

Abstract: Background: Osteoblast and osteoclast are the important factor in periodontal tissue remodeling for the orthodontic treatment success. Resorption process takes place in compression area by osteoclast and apposition in the tension

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In adult individuals, the microarchitecture of trabecular bone becomes thin, while cortical bone becomes thin and porous 24 . A previous in vivo study demonstrated that in response to mechanical stimuli, the alveolar bone of the young rats was more active and sensitive than that of the adult rats 4 . As the aging process progresses, the periodontal ligament becomes more fibrotic and may influence how the tissues react to orthodontic forces 25 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In adult individuals, the microarchitecture of trabecular bone becomes thin, while cortical bone becomes thin and porous 24 . A previous in vivo study demonstrated that in response to mechanical stimuli, the alveolar bone of the young rats was more active and sensitive than that of the adult rats 4 . As the aging process progresses, the periodontal ligament becomes more fibrotic and may influence how the tissues react to orthodontic forces 25 .…”
Section: Discussionmentioning
confidence: 94%
“…In general, results demonstrated that in the subjects receiving soybean isoflavone genistein, TGF-β1 levels were significantly higher than the other groups. A previous study found that genistein can significantly increase the number of osteoblasts during orthodontic tooth movement 4 . Soybeans are the most common source of isoflavones, which have Values are presented as mean ± standard deviation or p-value only.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…At the next stage, the subjects were anesthetized with ketamine and orthodontic movement was set by installing the band matrix and orthodontic bracket on each mandibular incisor to enable it to move distally using an open coil spring (Ortho-tech, America) 15 with a power of 0.0525 N or 52.5 grams ( Figure 1). Observations were then made after the subjects had been sacrificed on Days 15 and 22 by extracting both their right and left mandibular incisors as well as periodic tissue and placing these in the fixative solution.…”
Section: Methodsmentioning
confidence: 99%